Editorial - Miranda, Diego (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
The Sociedad Colombiana de Ciencias Hortícolas (Colombian Society for Horticultural Science) and the Universidad Pedagógica y Tecnológica de Colombia present the third edition of the Revista Colombiana de Ciencias Hortícolas-RCCH (Colombian Journal of Horticultural Science) for the year 2022, which calls for the worrying statistics on food insecurity and access to a healthy diet in Latin America. According to FAO reports, the COVID-19 pandemic was the most critical moment with 28% of hunger compared to the world average of 23%.